Työllisten maahanmuuttajien määrä on kasvanut Suomessa - Aki Kangasharju; Antti Kauhanen; Aino Kalmbach; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2023)
– The decline of working age population makes it difficult to find employees. In this report we analyze the evolution of immigrant employment in Finland and the fiscal impact of immigration as well as the effect on the labor market. We show that the number of employed immigrants as well as immigrants' employment rate in Finland has increased. We review the economic impacts of immigration. We show that the fiscal impact of immigration depends heavily on the characteristics of immigrants and the time of immigration and therefore no general conclusions can be made on the economic impact. However, we show that full-time employees pay more taxes than receive direct income transfers and therefore their direct fiscal impact is positive. This is true also for employees employed at the lowest pay grades in the collective agreements.
Keywords: J61; E24; 330; Immigration; Employment; Public finance